PEMBUATAN SELULOSA ASETAT DARI α -SELULOSA TANDAN KOSONG KELAPA SAWIT - M Roganda L Lumban Gaol, Roganda Sitorus, Yanthi S, Indra Surya, Renita Manurung (Universitas Sumatera Utara, 2013)
Utilization of empty fruit bunches of oil palm in Indonesia is still very low, so it should be developed further. One of them by researching the manufacture of cellulose acetate from oil palm empty fruit bunches. The process used in this study is the cellanase with α-cellulose materials. Stages reaction is activation, acetylation, hydrolysis, neutralization and drying. Activation in thethree-neck flask with the addition of 50 ml of glacial acetic acid and stirredfor 3 hour,then added 15 ml of acetic acid anhydride as acetylation agent. Acetylation performed with the variation of time, 2, 2.5, 3, 3.5 hours. In the hydrolysis step, add 2 ml of water and5 ml of glacial acetic acid. The reaction lasted for 30 minutes, then added 1 g of sodium acetate for neutralization, neutralization lasts for 5 minutes. Then do the washing up to the smell of acetic acid is lost, and the last stage is the drying is done with a temperature below 50 oC. The resulting products are then analyzed the degree of substitution, melting point, and then carried out FTIR analysis. The results obtained when the optimum conditions for the acetylation reaction is 2.5 - 3 hours.